Measuring Method for Helical Angle Parameter of Helical Gear based on Machine Vision - Wei Shi; Yu Hou; Shifan Zhou; Qilang Liu (Jixie chuandong, 2020)
Abstract In order to detect helical angle and other parameter quickly， the method of measuring standard helical gear is proposed based on machine vision. First of all， the overall structure and measurement process of the system are introduced. The digital image of upper gear face and lower gear face are morphologically processed to obtain the main characteristic parameters of the helical gear， and then， the helical angle is obtained. Experimental show that the method has high accuracy and efficiency， and can meet the needs of measurement requirement.